Unification of Italy - Gooch, John, 1945- (Lancaster pamphlets., 1986)
John Gooch's book is a concise introduction to the unification of the Italian states and the legacy of this union. Starting in 1815 at the end of the Napoleonic Wars, the book goes on to explain how, despite the causes of disunity, these Italian states shared racial, linguistic, and cultural factors, which led to their eventual political unity.